Mitral valve prolapse and joint hypermobility: evidence for a systemic connective tissue abnormality?. Issue 4 (August 1982) - Pitcher, D; Grahame, R
Abstract : Clinical evidence for an abnormally of extracardiac connective tissue was sought in 21 patients with idiopathic mitral valve prolapse and was compared to that in 21 matched controls. The incidence of rheumatic and orthopaedic complaints and the prevalence of hypermobile joints, Marfanoid habitus, and skeletal deformity were compared in the 2 groups. Skin thickness and elasticity were measured, and the mean values in the 2 groups were compared. hypermobile joints were significantly commoner in patients with mitral valve prolapse. Easy bruising was reported significantly more commonly by patients with mitral prolapse; the incidence of other rheumatic complaints was similar in the 2 groups. There was no significant difference in skin thickness, skin elasticity, and the prevalence of either skeletal deformity or Marfanoid habitus between patients with mitral valve prolapse and controls. The results support previous evidence of an association between mitral valve prolapse and benign hypermobility of the joints, but emphasise that many patients with mitral valve prolapse have no clinically apparent connective tissue abnormality outside the heart. It remains uncertain whether the valve lesion in these patients represents a tissue-specific abnormality of mitral valve collagen or the only clinical expression of a minor systemic connective tissue abnormality.